The Franco-Libyan Relations - (:unkn) unknown (My University, 2008)
Franco-Libyan relations, have gone through periods of cooperation and tension and sometimes even conflict. These relationships are particularly experienced periods of cooperation and neighborhood during the 17th century. They have also gone through periods of armed conflict in the late 19th century and early 20th century, between certain Libyan tribes and the French forces on the territory of Chad. France has also played an important role in the liberation of Libya with the Allied forces during World War II. And after periods of conflict, the Franco-Libyan oscillate between cooperation and conflict. The lack of stability relations political, economic and cultural. Libya and now is the best choice for cooperation with European countries on the other side of the Mediterranean and working together for the safety of the Mediterranean basin. Today, there is an opportunity to strengthen this relationship, especially both parties share many common interests of the two countries' foreign policy calling for joint work, such as Africa, the African Union, the file illegal immigration, Mediterranean cooperation, dialogue Five + Five and the Arab Maghreb Union.
Keywords: African Research